Immune and Hematological Reconstitution after Allogenic Bone Marrow Transplantation in Tunisian Pediatric Recipients: Prospective Study and Tunisian Experience Report - Jenhani, F.; Regaya, Z.; Berraies, L.; Mellouli, F. (Journal of Hematology Research, 2017)
AIM: A regular monitoring of the immune reconstitution mainly based on the quantitative determination of lymphocyte T subpopulation. This is prospective analysis for 1 year in Tunisian children treated with allogenic intrafamilial bone marrow transplantation. Methods: We conducted a prospective analysis for 1 year follow up enrolling 25 children treated with allogenic intrafamilial bone marrow transplantation among them two cases of Peripheral hematopoietic transplantation and placental cord blood transplantation including: aplastic anemia (6 cases), hemoglobinopathies (12 cases), myelodysplastic syndrome (1 case), 2 cases of Acute lymphocytic leukemia, a case of congenital amegacarycytosis and 3 cases of primary immunodeficiency with lack of expression of major MHC class II. All subjects received different conditioning regimens according to the indication. Our study consisted of a regular monitoring of the immune reconstitution mainly based on the quantitative determination of lymphocyte T subpopulation. So, these tests were routinely requested to 1 month, 2 months, 3 months, 6 months, 9 months and 12 months post- bone marrow transplantation. Results: The average time of engraftment was 18 days corresponding to neutrophil recovery (12-24). For the T cell recovery, a rate of CD4 + T lymphocytes > 200/ mm3 was provided within an average of 2.5 months (1-7). The average time to obtain CD8+ T lymphocytes >200 /mm3 was 2 months (1-5). The humoral immune reconstitution was made within an average of 2 months (1-4). A ratio of CD4+ / CD8+ T lymphocytes (>1) was obtained within 10 months and a half (1-24). Univaried analysis showed a significant correlation between the bone marrow sex matched and the faster reorganization of CD8 + T cells (p = 0.042). Moreover, a quantity of CD34 +> 6x 106/ kg was significantly associated with the recapture of a formula lymphocyte T CD4+ / CD8+ (> 1) (p=0.03). Conclusion: The immune recovery post bone marrow transplantation in children began with myeloid lineage then lymphoid B then lymphoid T. The inversion of the ratio CD4 +/CD8+ T lymphocytes, seemed to be influenced on the one hand by the high content of CD34 + cells in the graft as well as the type of conditioning on the other hand by the CMV infection since it accelerates significantly CD8+ T lymphocyte reconstitution.